Sistematización del proceso de participación ciudadana y política de la mancomunidad de la cuenca del lago San Pablo, período 2011-2013 - Rivadeneira Burbano, Gabriela Alejandra (2015)
This research summarizes the associative experience commonwealth of rural parishes of San Rafael de la Laguna, San Pablo del Lago, González Suarez and Eugenio Espejo and its role in building the Good Living Rural communities, indigenous peoples and nationalities and Afro-Ecuadorian. In chapter 1 the theoretical bases of citizen participation, local development, public policy, public intercultural which are reflected in the concept of pooling, already present in Latin American communities and our initial outbreak in Ecuador are determined. Since the seventies this movement gains strength profound social connotations in our America and the trend of Community Curriculum is activated. In Ecuador, the theoretical implications of commonwealth become visible, more strongly, since the implementation of the 2008 Constitution and the creation of the National Plan of Good Living. In chapter 2 the process of forming the Commonwealth of GAD Basin Lake San Pablo, with the inclusion of a diagnostic study that is considered a sign of inhabitants and authorities of the four parishes aforementioned develops. The approach of the results of the application of surveys and interviews with their respective charts, graphs and interpretations are made. In this chapter information on the geographic, economic, historical and cultural reality of the four parishes of the cash-generating experience is also presented. Chapter 3 outlines the learning that leaves the experience gained and synthesizes public or community learning related to the commonwealth, with citizen participation and local development. Projects why it is important to share lessons learned. The fourth and final chapter sets out the conclusions and recommendations that it comes after the conclusion of the research.